Central Giant Cell Granuloma of Mandible: A Case Report (Bangladesh Journal of Dental Research & Education, 2013)
Central Giant Cell Granuloma (CGCG) is a benign tumour of the jaws. It is relatively uncommon. The most common site involved is anterior part of mandible, especially in females under 30 years of age. The aim of this paper is to present such an uncommon entity in 25 year old Indian female and the diagnostic challenges it posed as it mimics various giant cell lesions of genetic disorders with its treatment options. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16615 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 57-59